Computer Science
Reduce the following boolean expression to its simple form:
A.[B + C.(A.B + A.C')]
Boolean Algebra
12 Likes
Answer
A.[B + C.(A.B + A.C')]
= A.[B + A.B.C + A.C'.C] [Distributive Law]
= A.[B + A.B.C + 0] [Complementary Law: C'.C = 0]
= A.[B(1 + AC)] [Distributive Law]
= A.B [∵ 1+AC=1]
Answered By
11 Likes
Related Questions
Convert (X' + Y + Z').(X + Y' + Z).(X + Y + Z').(X + Y + Z) into SOP form.
Simplify the following expression using laws of boolean algebra:
(a.b + x + y + z).(a.b + x'.y'.z')Find the complement of F (a, b, c, d) using Demorgan's Laws. Show the relevant reasoning.
F(a, b, c, d)=a + {(b + c).(b' + d')}Simplify a.b + a'.c + b.c using the laws of boolean algebra. At each step, state clearly the law used for simplification.